![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
A=\(x^2+y^2+z^2+2xy+2yz+2xz\)
B=\(x^2+y^2+z^2-2xy+2yz-2xz\)
C=\(x^2+y^2+z^2-2xy-2yz+2xz\)
D=\(x^2+4y^2+1+2x-4y-4xy\)
TL:
\(A=x^2+y^2+z^2+2xy+2yz+2xz\)
\(B=x^2+y^2+z^2-2xy+2yz-2xz\)
\(C=x^2+y^2+z^2-2xy-2yz+2xz\)
\(D=x^2+1+4y^2+2x-4y+4xy\)
hc tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
a. (x + y)2 = x2 + 2xy + y2
b. (x - 2y)2 = x2 - 4xy - 4x2
c. (xy2 + 1)(xy2 - 1) = x2y4 - 1
d. (x + y)2(x - y)2 = (x2 + 2xy + y2)(x2 - 2xy + y2) = x4 - (2xy + y2)2 = x4 - (4x2y2 + y4) = x4 - 4x2y2 - y4
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\left(3x+1\right)^3=9x^3+9x^2+9x+1\)
\(b,\left(\frac{2}{3}x+1\right)^2=\frac{4}{9}x^2+\frac{4}{3}x+1\)
\(c,\left(x-y\right)^2-\left(x+y\right)^2=\left(x-y-x-y\right)\left(x-y+x+y\right)=-2y\cdot2x=-4xy\)
\(d,\left(x+y\right)^2-\left(x-y\right)^2=\left(x+y-x+y\right)\left(x+y+x-y\right)=2y\cdot2x=4xy\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x^3-1\right)\left(x^3+1\right)=\left(x^3\right)^2-1^2=x^6-1\)
\(\left(x^3-1\right)\left(x^3+1\right)\)
\(=\left(x^3\right)^2-1^2\)
\(=x^3-1\)
Z thôi T nha
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(\left[\left(a+b\right)-c\right]^2=\left(a+b\right)^2-2c\left(a+b\right)+c^2\)
\(=\left(a^2+2ab+b^2\right)-2ac-2bc+c^2\)
\(=a^2+b^2+c^2+2ab-2ac-2bc\)
2)Phần này tg tự
3)\(\left(x+y+z\right)\left(x+y-z\right)=\left(x+y\right)^2-z^2=x^2+2xy+y^2-z^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, (x+y)2 = x2 + 2xy + y2
b, ( x-4y)2= x2 -8xy2 + 16y2
c, \(\left(3x+\frac{1}{3}\right)^2=9x^2+2xy+\frac{1}{9}\)
d,\(4x^2-81=\left(2x-9\right)\left(2x+9\right)\)
e,\(\left(xy+5\right)^2=x^2y^2+10xy+25\)
f,\(\left(x-y+z\right)^2=x^2+y^2+z^2-2xy+2xz-2yz\)
g,\(1-9y^2=\left(1-3y\right)\left(1+3y\right)\)
h,\(\left(m-\frac{2}{3}n\right)^2=m^2-\frac{4}{3}mn+\frac{4}{9}n^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x - 1/2x²y)²
= x² - 2x . 1/2 x²y + (1/2x²y)²
= x² - x³y + 1/4 x⁴y²
b) (2xy² - 1)(1 + 2xy²)
= (2xy²)² - 1²
= 4x²y⁴ - 1
c) (x - y + 2)²
= (x - y)² + 2(x - y).2 + 2²
= x² - 2xy + y² + 4x - 4y + 4
= x² + y² - 2xy + 4x - 4y + 4
d) (x + 1/2)(1/2 - x)
= (1/2)² - x²
= 1/4 - x²
e) (x² - 1/3)²
= (x²)² - 2x².1/3 + (1/3)²
= x⁴ - 2/3 x² + 1/9
Ta có : A = (x - 1 + y)2
= [(x - 1) + y]2
= (x - 1)2 + 2(x - 1)y + y2
= x2 - 2x + 1 + 2xy - 2y + y2
= x2 + y2 + 1 - 2x - 2y + 2xy
A = (x - 1 + y)2
= [(x - 1) + y]2
= (x - 1)2 + 2(x - 1)y + y2
= x2 - 2x + 1 + 2xy - 2y + y2
= x2 + y2 + 1 - 2x - 2y + 2xy